Yeast Immobilization Systems for Alcoholic Wine Fermentations: Actual Trends and Future Perspectives - Moreno-García, Jaime; García-Martínez, Teresa; Mauricio, Juan C.; Moreno, Juan (Frontiers in Microbiology, 2018)
Yeast immobilization is defined as the physical confinement of intact cells to a region of space with conservation of biological activity. The use of these methodologies for alcoholic fermentation (AF) offers many advantages over the use of the conventional free yeast cell method and different immobilization systems have been proposed so far for different applications, like winemaking. The most studied methods for yeast immobilization include the use of natural supports (e.g. fruit pieces), organic supports (e.g. alginate), inorganic (e.g. porous ceramics), membrane systems and multi-functional agents. Some advantages of the yeast-immobilization systems include: high cell densities, product yield improvement, lowered risk of microbial contamination, better control and reproducibility of the processes, as well as reuse of the immobilization system for batch fermentations and continuous fermentation technologies. However, these methods have some consequences on the behavior of the yeasts, affecting the final products of the fermentative metabolism. This review compiles current information about cell immobilizer requirements for winemaking purposes, the immobilization methods applied to the production of fermented beverages to date, and yeast physiological consequences of immobilization strategies. Finally, a recent inter-species immobilization methodology has been revised; where yeast cells are attached to the hyphae of a GRAS fungus and remain adhered following loss of viability of the fungus. The bio-capsules formed with this method open new and promising strategies for alcoholic beverage production (wine and low ethanol content beverages).